Active packaging from polylactic acid biocomposite film via supercritical fluids impregnation - Anuar, Hazleen (2019)
The demand for food safety by consumers promotes continuous improvement of active packaging systems for food product and is recently increasing. The safety issues of foodpackaging industries directed the attention towards biodegradable packaging applications. Therefore, this research aims to develop a polylactic acid (PLA) reinforced with durian skin fibre (DSF) biocomposite film for active food packaging. In the biocomposite, epoxidized palm oil (EPO) was added as a plasticizer and cinnamon essential oil (CEO) was added as an antimicrobial agent. Supercritical carbon dioxide (SCCO2) method was employed as treatment oi improve dispersion of DSF in the biocomposite. The effect of DSF content, EPO and CEO were studied in terms of thermal, structural, mechanical, and functional properties of the PLA biocomposite film. The PLA biocomposites were produced via solvent casting method. The process started with the optimization of DSF content, EPO, and CEO based on the tensile test. Design Expert software version 6.0.8 via response surface method (RSM) was used to analyse and determine the highest values of tensile strength and tensile modulus. The selected optimum values were at 3 wt % DSF, 5 wt % EPO, and 1 wt % CEO. The P-value of both responses was less than 0.05, while the coefficient, R2 , is nearly 1.0 which confirms that the tensile properties model is significant. Once optimized, the PLA biocomposites were treated by supercritical carbon dioxide. The conditions of CO2 treatment on for PLA biocomposite were conducted at 2 conditions under 40 oC temperature and at 100 bar and 200 bar pressure. Tensile properties of PLA-DSF biocomposite improved by about 5% after SCCO2 treatment at condition 1 (40 oC; 100 bar). Scanning electron micrograph revealed that a porosity was induced in SCCO2 treated PLA biocomposite. The elongation of treated PLA-DSF biocomposite increased with the addition of EPO and CEO. The presence of aldehyde as a functional group was evident in Fourier transform infrared (FTIR) analysis spectroscopy. From thermogravimetry analysis (TGA), the SCCO2 treated biocomposite with the addition of DSF, EPO and CEO at condition 2 (40oC; 200 bar) has resulted the lowest weight loss due to the degradation effect of thermal. Differential scanning calorimetry (DSC) analysis shows that the SCCO2 treated biocomposite possessed the highest crystallinity as compared to untreated biocomposite. Similarly, tensile strength of the SCCO2 treated biocomposite also possess high tensile strength. Water absorption test showed that the sample untreated with DSF of PLA biocomposite absorbs most water as compared to other compositions with 5.1%. This is due to the hydrophilic nature of fibre that easies to absorb water molecules. Soil burial test showed that the sample of treated PLA and DSF possessed the highest value of weight losses after 80 days with 97.8 %. Biocomposite with CEO demonstrated antimicrobial activity against both gram-positive and gram-negative bacteria. The treated PLA biocomposite is whiter, indicating the potential as an active food packaging material. The supercritical fluid treatment of PLA biocomposite is significant for active packaging industries to ensure the packaging meets the requirement by consumers and is eco-friendly.